Analysis of the Breakage Data of a Series of Devices - L. S. Bbosa (International Mineral Processing Congress, 2014)
Single particle impact breakage experiments provide essential data to aid in understanding of rock fracture in comminution. Such experiments, conducted using devices such as the drop weight tester, split Hopkinson bars and more recently the rotary breakage tester, have been successfully used to characterize ore breakage properties in relation to measured fracture energies. The work presented in this paper highlights the techniques behind the calculation of impact breakage properties from each of these three devices. The breakage parameters that can be calculated from experimental data from each of these are to be described. Drop weight tests are used to calculate A and b hardness parameters using the standard JK breakage model. Split Hopkinson pressure bars are used to establish the ultimate compressive stress of particles through single impact breakage tests and the fraction of impact energy utilized to cause particle fracture. Low energy breakage tests using the rotary breakage tester are shown to be used in calculating particle breakage probability. Methods to calculate parameters related to particle breakage probabilities such as E0 and Ecrit are also discussed.